(untitled) (Scientific journal of the Fergana State University, 2024)
The article presents new principles of humanization of social structures, laws of the market economy, changing ideological and moral principles, unemployment, material shortage, uncontrollable children, separation of families, anti-social phenomena such as alcoholism, drug addiction, crime, prostitution social problems are scientifically analyzed.